(untitled) (Advances in Military Technology, 2020)
This paper focuses on reducing the corrosion rate of aluminium alloy 6061 through anodizing. The study involves characterizing corrosion phenomenon that occurs on aluminium alloy 6061 in relation to parameters involved in an anodizing process, in particular the current density of anodizing, and its corrosion environment; specifically, the concentration and pH value of the corrosion accelerator. The experiment samples were anodized in sulphuric acid (H2SO4) at a current density ranging from 0.012 A/mm2 to 0.018 A/mm2. The paper also includes a qualitative analysis of corrosion images obtained from the experiment through scanning electron microscope. It concludes that corrosion rate may be reduced through an increase of current density during anodizing.